The Influence of Digital Technology on Children's Behavior in Cirebon Regency: A Study from the Perspective of Criminology Law for Preventing Deviant Behavior - Rofii, Apip; Khanan, Abdul; Ramadhan, Axelceri (Jurnal Legisci, 2025)
Background. The development of digital technology in recent years has had a significant impact on children's behavior, including in Cirebon Regency. Although digital technology offers various benefits, such as easy access to information and entertainment, its negative impacts, especially on children's behavior, are increasingly felt. Cases of child exploitation through social media, the increase in violence involving teenagers, and the influence of violent content on digital platforms have become major concerns. Aim. This research aims to examine the influence of digital technology on children's behavior in Cirebon Regency between 2020 and 2025. Methods. The research method used is a mixed methods approach, which combines qualitative and quantitative approaches. Data were obtained through interviews with the police, the Education Office, the Regional Indonesian Child Protection Commission (KPAID), as well as parents and affected children. In addition, a questionnaire survey was conducted to obtain data on the patterns of technology use by children and teenagers. Result. The research results show that the lack of parental supervision, low digital literacy, and exposure to violent and exploitative content in cyberspace are the main factors causing deviant behavior in children. Conclusion. This research recommends the creation of regulations governing the use of digital technology by children, including restrictions on the duration of mobile phone use and monitoring of accessible content. Implication. Efforts to improve digital literacy and cooperation between the government, society, and families have also been identified as important steps in preventing the negative impact of digital technology on children's behavior.